Social-perception and Mental Health of the Urban Homeless People in Almeria - Salvador Ferrer, Carmen María; Jurado Pérez, María Daniela; Rodríguez Fernández, Ascensión; Martínez Crisol, Juan José (Cuadernos de Trabajo Social, 2025)
The present work aims to know the perception of homeless people in the province of Almeria with respect to social-personal elements (motivating factors of the situation; stigma and discrimination; health and well-being and empowerment and dignity) and their relationship with the time they have lived on the streets and attendance at mental health centres. A questionnaire was applied to count homeless people across the country. The dates indicate that people suffer discrimination, especially insults. In addition, we found that most people have mental health problems. In the same way, it seems that there is a relationship between attendance in mental health centres, the time they have been in this situation, and degrading acts. These data indicate that it is necessary to promote holistic, participatory, and integrative approaches where personalised interventions are promoted to achieve human dignity.